CHALLENGES OF ACCESS AND QUALITY IN THE DEVELOPMENT OF EARLY CHILDHOOD EDUCATION (ECE) IN INDONESIA - Suli, Siti Fardianti; Abdullah, Marsya; Latoko, Fitriani AR.; Mahmud, Ningsi; Uduala, Arifin; Airmas, Alya; Lestari, Nisa Ayu (Academic Solution Publisher, 2025)
Early Childhood Education (PAUD) is a crucial stage in human resource development, as it is during this period that the foundation for a child's cognitive, social, emotional, and moral development is formed. However, the implementation of PAUD in Indonesia still faces serious challenges, both in terms of access and quality of services. This study aims to examine various obstacles that hinder the equitable distribution and improvement of the quality of PAUD in Indonesia. The approach used is a qualitative descriptive with a literature study method, involving secondary data sources from scientific journals, policy documents, and reports from relevant national and international institutions. The results of the analysis indicate that geographical disparities between urban and rural areas, especially in the 3T (Disadvantaged, Frontier, Outermost) regions, are the main obstacles in accessing PAUD services. In addition, limited family economic resources and high operational costs also impact the low participation of children in PAUD institutions. From the quality aspect, low teacher qualifications and competencies, inadequate welfare of educators, and suboptimal curriculum implementation are key issues that require serious attention. The governance of early childhood education institutions and quality assurance systems are also still not effectively integrated. This study recommends the need for a collaborative strategy between the central and regional governments, communities, and the private sector to expand access and improve the quality of early childhood education services in Indonesia. These efforts need to be supported by supportive policies, adequate funding, ongoing teacher training, and a participatory quality evaluation system.